Dual-probe molecular MRI for the in vivo characterization of atherosclerosis in a mouse model: Simultaneous assessment of plaque inflammation and extracellular-matrix remodeling - Reimann, Carolin; Brangsch, Julia; Kaufmann, Jan O.; Adams, Lisa C.; Onthank, David C.; Thoene-Reineke, Christa; Robinson, Simon P.; Hamm, Bernd; Botnar, Rene M.; Makowski, Marcus R. (Scientific Reports, 2019)
Molecular MRI is a promising in-vivo modality to detect and quantify morphological and molecular vessel-wall changes in atherosclerosis. The combination of different molecular biomarkers may improve the risk stratification of patients. This study aimed to investigate the feasibility of simultaneous visualization and quantification of plaque-burden and inflammatory activity by dual-probe molecular MRI in a mouse-model of progressive atherosclerosis and in response-to-therapy. Homozygous apolipoprotein E knockout mice (ApoE−/−) were fed a high-fat-diet (HFD) for up to four-months prior to MRI of the brachiocephalic-artery. To assess response-to-therapy, a statin was administered for the same duration. MR imaging was performed before and after administration of an elastin-specific gadolinium-based and a macrophage-specific iron-oxide-based probe. Following in-vivo MRI, samples were analyzed using histology, immunohistochemistry, inductively-coupled-mass-spectrometry and laser-inductively-coupled-mass-spectrometry. In atherosclerotic-plaques, intraplaque expression of elastic-fibers and inflammatory activity were not directly linked. While the elastin-specific probe demonstrated the highest accumulation in advanced atherosclerotic-plaques after four-months of HFD, the iron-oxide-based probe showed highest accumulation in early atherosclerotic-plaques after two-months of HFD. In-vivo measurements for the elastin and iron-oxide-probe were in good agreement with ex-vivo histopathology (Elastica-van-Giesson stain: y = 298.2 + 5.8, R2 = 0.83, p < 0.05; Perls‘ Prussian-blue-stain: y = 834.1 + 0.67, R2 = 0.88, p < 0.05). Contrast-to-noise-ratio (CNR) measurements of the elastin probe were in good agreement with ICP-MS (y = 0.11x-11.3, R² = 0.73, p < 0.05). Late stage atherosclerotic-plaques displayed the strongest increase in both CNR and gadolinium concentration (p < 0.05). The gadolinium probe did not affect the visualization of the iron-oxide-probe and vice versa. This study demonstrates the feasibility of simultaneous assessment of plaque-burden and inflammatory activity by dual-probe molecular MRI of progressive atherosclerosis. The in-vivo detection and quantification of different MR biomarkers in a single scan could be useful to improve characterization of atherosclerotic-lesions.
CRIS-Team Scopus Importer:2023-03-08